VRM: a failure-aware Grid resource management system. (29th December 2008) - Burchard, Lars-Olof; Heiss, Hans-Ulrich; Linnert, Barry; Schneider, Joerg; , Cesar A.F. De Rose
For resource management in Grid environments, advance reservations turned out to be very useful and hence are supported by a variety of Grid toolkits. However, failure recovery for such systems has not yet received the attention it deserves. In this paper, we address the problem of remapping reservations to other resources, when the originally selected resource fails. Instead of dealing with jobs already running, which usually means checkpointing and migration, our focus is on jobs that are scheduled on the failed resource for a specific future period of time but not started yet. The most critical factor when solving this problem is the estimation of the downtime. We avoid the drawbacks of under- or over-estimating the downtime by a dynamic load-based approach that is evaluated by extensive simulations in a Grid environment and shows superior performance compared to estimation-based approaches.